Wydział Teologiczny Uniwersytetu Opolskiego - Pośpiech, Remigiusz (Studia Nauk Teologicznych PAN, 2020)
Th e Th eological Faculty of Th e Opole University has existed since 1994. The full academic rights were obtained in 2001. Th e Faculty encompasses 17 departments and 2 academic units. Two major courses are taught: theology and family science. Th e Faculty issues 5 journals and 8 book series. About 30 books are published every year. An important area of academic research is the history of the Church and liturgy in Silesia. Th e Faculty cooperates with Polish and overseas academic institutions. One of the most important events was the conferring of an Honorary Doctorate on John Paul II by the Opole University as the initiative of the Th eological Faculty.